2000
DOI: 10.1063/1.1324457
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamical properties of SrTiO[sub 3] thin films

Abstract: We report the experimental studies of the vibrational spectra of SrTiO 3 films grown by pulsed laser deposition. Raman scattering, with and without bias electric field, and Fourier-transform far-infrared ellipsometry between 30 and 700 cm −1 have been utilized for investigation of the phonon behavior. These results are discussed in connection with the low-frequency dielectric properties of the SrTiO 3 films. In the films, the soft mode reveals hardening compared to that in bulk crystals. This observation is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…According to reports on the lattice dynamics of ST films, the soft mode of the films is usually much harder than that in the bulk materials at low temperature [ 14 , 15 , 16 , 17 , 18 , 19 ]. Correspondingly, the phonon contribution to the low-temperature dielectric permittivity is strongly suppressed in ST films compared to bulk ST. For epitaxial films deposited by pulsed laser deposition (PLD), it was explained by influence of some specific local polar regions occurring in ST thin films during the deposition process [ 15 ]. For polycrystalline films, porosity and eccentricity of the grain boundaries are suggested as the main reasons for such behaviour [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to reports on the lattice dynamics of ST films, the soft mode of the films is usually much harder than that in the bulk materials at low temperature [ 14 , 15 , 16 , 17 , 18 , 19 ]. Correspondingly, the phonon contribution to the low-temperature dielectric permittivity is strongly suppressed in ST films compared to bulk ST. For epitaxial films deposited by pulsed laser deposition (PLD), it was explained by influence of some specific local polar regions occurring in ST thin films during the deposition process [ 15 ]. For polycrystalline films, porosity and eccentricity of the grain boundaries are suggested as the main reasons for such behaviour [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For polycrystalline films, porosity and eccentricity of the grain boundaries are suggested as the main reasons for such behaviour [ 18 ]. Sirenko et al reported that at high temperatures the soft-mode frequency in the film and the bulk are close at zero electric field, indicating that either the density of the local polar regions is low or the polarization of these regions is weak or small [ 15 ]. However, whereas the electric-field hardening of the soft mode vanishes in ST crystals above T ≈ 80 K [ 20 ], it persists in ST thin films until high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation